Impossible Images: Radio Astronomy, the Square Kilometre Array and the Art of Seeing. Issue 4 (4th July 2019) - Twidle, Hedley
Abstract : In South Africa's arid central Karoo, astronomers and engineers are slowly building the biggest scientific instrument in the world. The Square Kilometre Array (SKA) will one day link radio telescopes across the southern hemisphere, turning much of the planet into a vast ear for picking up the faintest echoes from the early universe. This article explores the conceptual and representational challenges posed by radio astronomy in general and the SKA in particular. What kinds of cultural artefacts and images are likely to be produced by the SKA, and what kind of relationship will a non-specialist audience have with them? How can the Array's unprecedented power to look (or listen) back in time be related to the deep human past that has left traces all through the Karoo landscape? Working through a series of images, my enquiry moves from optical astronomy in Cape Town and Sutherland to the radio dishes near Carnarvon, tracing a history of picturing the cosmos and the southern skies. I explore how questions of visuality, imagination and aesthetics might be introduced to the languages of science, policy and public relations, in which this project is most often discussed, and argue that the project (in terms of a cultural response) asks for more than the journalistic, the literal or the merely informational. It challenges writers and artists to work at the limits of representation and to find ways of registering the incommensurate scales and meanings compacted into a Karoo landscape that has often been figured as 'empty' but now seems full of noise, data and politics.